2006
DOI: 10.1002/imhj.20096
|View full text |Cite
|
Sign up to set email alerts
|

Maternal limit-setting in toddlerhood: Socialization strategies for the development of self-regulation

Abstract: Early findings from the Prohibition Coding Scheme (PCS; Houck & LeCuyer, 1995; LeCuyer‐Maus & Houck, 2002; Medvin & Spieker, 1985) revealed that maternal limit‐setting styles with toddlers were differentially related to later child social competence, self‐concept, and delay of gratification. For this study, the PCS was revised to provide more information about the specific strategies mothers used during limit‐setting in relation to those outcomes. Results from the PCS‐Revised (PCS‐R; LeCuyer & Houck, 2004) inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 41 publications
5
39
0
Order By: Relevance
“…Mechanisms by which external behavioral expectations and guidelines are transmitted by mothers to children, such as clear and consistent limit-setting, have been found to help channel children's behavior in ways that reinforce and guide the development of self-regulation (Kopp 1982;Lecuyer and Houck 2006). Thus, external regulation, in the form of maternal monitoring behavior, may help children to internalize regulatory strategies and guidelines which can guide their development in an adaptive direction (Grolnick and Farkas 2002).…”
Section: Maternal Parenting Practices and Parental Monitoringmentioning
confidence: 93%
See 1 more Smart Citation
“…Mechanisms by which external behavioral expectations and guidelines are transmitted by mothers to children, such as clear and consistent limit-setting, have been found to help channel children's behavior in ways that reinforce and guide the development of self-regulation (Kopp 1982;Lecuyer and Houck 2006). Thus, external regulation, in the form of maternal monitoring behavior, may help children to internalize regulatory strategies and guidelines which can guide their development in an adaptive direction (Grolnick and Farkas 2002).…”
Section: Maternal Parenting Practices and Parental Monitoringmentioning
confidence: 93%
“…On the other hand, nurturing, consistent, and authoritative discipline practices have been found to promote self-regulation (Bernier et al 2010;McCabe et al 2004). For instance, maternal limit setting and sensitive responsiveness have been identified as a means of channeling children's behavior in ways that contribute to the development of self-regulation (Lecuyer and Houck 2006). Moreover, parental involvement is associated with adolescents' self-regulation, which in turn is linked with important adolescent developmental outcomes such as substance abuse, academic performance, and disruptive classroom behavior (Wong 2008).…”
Section: Maternal Characteristics and Children's Self-regulationmentioning
confidence: 98%
“…However, in light of the increasingly documented impact of environmental input on children's brain development (Chugani et al, 2001;Marshall & Fox, 2004) and the protracted postnatal development of prefrontal areas in particular (Duncan, 2001;Paus et al, 1999), some authors have suggested that the study of environmental influences, particularly early parent-child relationships, is likely to be useful in understanding individual differences in children's EF (Carlson, 2003;Fonagy & Target, 2002;Glaser, 2000) and related higher mental functions (Fernyhough, 1996;Fernyhough, 2008). Indirect support for the putative role of parent-child relationships in EF development stems from studies that have found parenting to relate to constructs bearing many similarities to some components of EF, labeled (for instance) as self-regulation (Jennings et al, 2008;LeCuyer & Houck, 2006) or effortful control (Kochanska et al, 2000;Poehlmann et al, 2010), or referring to child performance on cognitive tasks similar to those used to measure EF (Diaz, Neal, & Vachio, 1991). In addition, a very recent body of research is beginning to provide direct support for the idea that parenting plays an important role in the development of child EF per se (e.g., Bernier et al, 2010;Bernier, Carlson, Deschênes, & Matte-Gagné, in press;Bibok, Carpendale, & Müller, 2009;Hughes & Ensor, 2009;Landry, Miller-Loncar, Smith, & Swank, 2002).…”
Section: Antecedents Of Child Efmentioning
confidence: 96%
“…Although the larger family environment may have important associations with children's executive functioning, studies have shown that positive parenting, parental warmth, expressivity and support are significantly related to better attention control (Eisenberg et al, 2005), fewer problem behaviours (Gadeyne, Ghesquiere, & Onghena, 2004) and better self-control (LeCuyer & Houck, 2006). Specifically, mothers who support their children's autonomy (Joussemet, Koestner, Lekes, & Landry, 2005) and who demonstrate authoritative parenting (Bean, Bush, McKenry, & Wilson, 2003) generally have children who do better academically.…”
Section: Parenting Practicesmentioning
confidence: 97%